Gastric emptying and intestinal transit of pancreatic enzyme supplements in cystic fibrosis. Issue 2 (1st February 1999) - Taylor, C J; Hillel, P G; Ghosal, S; Frier, M; Senior, S; Tindale, W B; Read, N
Abstract : OBJECTIVE: To investigate gastric emptying and intestinal transit of pelleted pancreatin in relation to food boluses. Methods— Dual isotope scintigraphy combined with breath hydrogen sampling was used to track the concurrent gastric emptying and intestinal transit of 111 indium labelled microspheres and a 99m technetium labelled tin colloid test meal. Twelve pancreatic insufficient cystic fibrosis patients aged 5 to 38 years performed the study. RESULTS: 50% gastric emptying times showed patient to patient variation. The mean discrepancy in 50% gastric emptying times between the two labels was > 67 minutes. Mean small bowel transit time for the food bolus was prolonged at 3.6 minutes. A significant correlation was seen between weight standard deviation score and 50% emptying time for pancreatin ( r  = +0.73). Conclusion— Gastric mixing of food and pancreatin may be limited by rapid emptying of microspheres. Patients with high dosage requirements could benefit from changing the pattern of their pancreatin supplementation.